Low-cost Sensor System for Non-invasive Monitoring of Cell Growth in Disposable Bioreactors. (2015) - Reinecke, T.; Biechele, P.; Schulte, V.; Scheper, T.; Zimmermann, S.
Abstract: To ensure productivity and product quality, the parameters of biotechnological processes need to be monitored. Along temperature or pH, one important parameter is the cell density in the culture medium. In this work, we present a low-cost sensor system for online cell growth monitoring in bioreactors via permittivity measurements based on coplanar transmission lines. To evaluate the sensor, E. coli cultivations are performed. We found a good correlation between optical density of the culture medium and the effective permittivity at a frequency of 1 kHz when the sensor is submerged into the culture medium. Measurements at higher frequencies additionally allow monitoring the osmolarity. Furthermore, an improved sensor was successfully used for first non-invasive measurements through the polymer wall of a disposable bioreactor.